1992
DOI: 10.1002/cjce.5450700403
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of the particles entrained from fluidized beds: Gas humidity effects

Abstract: Experimental results obtained with 65 μm sand and 69 μm cracking catalyst showed that the smallest particles were not the most easily elutriated from fluidized beds of mixed size particles. This is in contradiction with the assumption applied to existing models for the prediction of the flux and size distribution of particles elutriated from a fluidized bed. The smallest particles cannot be removed by elutriation from a mixture of particles of various sizes. The smallest particles may be agglomerated with larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the entrainment experiment, at a specific gas velocity, a portion of the carbon black is not separated as it attaches, but some particles are not attached to the alumina particle, and, thus, those are entrained outward from the reactor. Baron et al 12 also mentioned that it is difficult to elutriate fine particles, because they aggregate via the cohesive force between themselves. As can be observed in Figure 4, the entrainment rate of carbon black particles increases as the gas velocity increases, because a high gas velocity may crush the aggregated carbon black particles and also separates carbon black particles from alumina particles in the bed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the entrainment experiment, at a specific gas velocity, a portion of the carbon black is not separated as it attaches, but some particles are not attached to the alumina particle, and, thus, those are entrained outward from the reactor. Baron et al 12 also mentioned that it is difficult to elutriate fine particles, because they aggregate via the cohesive force between themselves. As can be observed in Figure 4, the entrainment rate of carbon black particles increases as the gas velocity increases, because a high gas velocity may crush the aggregated carbon black particles and also separates carbon black particles from alumina particles in the bed.…”
Section: Resultsmentioning
confidence: 99%
“…10 Geldart and Wong 11 determined that the entrainment flux of alumina first increases and then decreases as the fines content increases, because cohesive powders have strong interparticle forces and also have a tendency to form larger powder sizes. Baron et al 12 reported that the smallest particles are not the most easily entrained from a fluidized bed of mixed silica sand, FCC, and polyethylene particles, because of the agglomeration of fine powders.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms for collecting particles include interception, inertial impaction, diffusion, gravitational settling and electrostatic attraction; the efficiency of each mechanism is dominated by the characteristics of the particles, the collecting media and the treated gas, such as flow velocity and temperature. The interparticle forces, such as the van der Waal's, the liquid-bridging and the electrostatic force, determine the elutriation, which may also be affected by the species of particles [7], temperature [8], gas flow rate [9] and humidity [10]. These works addressed only the effect of various parameters on elutriation.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al [29] and Kunii et al [34] proposed entrainment models in the freeboard of fluidized bed based on the summary of previous experimental results, and discussed the origin of the ejected particles in the freeboard. Baron et al [35] found that the smallest particles were not the most easily elutriated from fluidized beds of mixed size particles. Baeyens et al [36] also found that the elutriation rate constant stabilized with decreasing particle size when the particle size was smaller than the critical size, and proposed an empirical correlation for the elutriation rate constant for group C particles.…”
Section: Introductionmentioning
confidence: 99%